Artistic ageing: a mixed methods study on the benefits of a locally-developed virtual intergenerational arts and heritage programme (ARTISAN) on the wellbeing of older adults in Singapore - Kooi, Joshua Han Wen (Nanyang Technological University, 2022)
Background: Studies, both local and overseas, have established the benefits of arts-based interventions on the wellbeing of older adults. However, with the COVID-19 pandemic forcing many interventions online, the benefits of a virtual arts-based intervention is a question yet to be answered. Objectives: The present study explores the benefits of a virtual rendition of a locally developed 5-week intergenerational arts and heritage intervention on the wellbeing of older adults in Singapore. Methods: 14 participants, aged 63-83, were recruited for this mixed-method design study. A battery of standardised assessments was administered to participants at three timepoints to investigate the impact of the intervention on their wellbeing. Responses of the participants across three timepoints were then analysed using Friedman’s test and Wilcoxon’s signed-rank test. Weekly group discussions and post-intervention feasibility group discussions were collected and analysed using thematic analysis. Findings: Quantitative analysis showed no statistical difference in emotional support, positive social interactions, affectionate support, self-esteem, psychological wellbeing and civic engagement. There was a statistically significant difference in National Heritage [χ2(2) = 6.43, p = .040]. and Cultural Homogeneity [χ2(2) = 10.90, p = .004] across the three time points. Thematic analysis of transcripts produced nine themes, grouped into five categories (Relational Benefits, Multigenerational Learning, Reaffirming Citizenship, Nurturing Artistic Creativity and Inspiring Hope). Jointly, both qualitative and quantitative results suggest that while benefits of virtual arts-based interventions are present, more efforts are still required to refine virtual arts-based interventions in Singapore. Keywords: virtual intervention, art-based intervention, older adults, mixed-method design, Singapore